2008
DOI: 10.1186/1479-5868-5-33
|View full text |Cite
|
Sign up to set email alerts
|

Validity and repeatability of the EPIC physical activity questionnaire: a validation study using accelerometers as an objective measure

Abstract: Background: A primary aim of the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort study is to examine the association between total physical activity levels (comprising occupational, household and recreational activity) and the incidence of cancer. We examined the validity and long-term repeatability of total physical activity measurements estimated from the past-year recall EPIC questionnaire, using accelerometers as an objective reference measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
149
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(164 citation statements)
references
References 41 publications
10
149
2
Order By: Relevance
“…The validity of the physical activity–related items of the questionnaire used in this cohort was assessed in studies finding a high correlation between self‐reported physical activity estimates with the accelerometer measurements of total metabolic equivalent in 182 participants22 and with combined heart rate and movement‐sensing measurements in 1941 participants 23…”
Section: Methodsmentioning
confidence: 99%
“…The validity of the physical activity–related items of the questionnaire used in this cohort was assessed in studies finding a high correlation between self‐reported physical activity estimates with the accelerometer measurements of total metabolic equivalent in 182 participants22 and with combined heart rate and movement‐sensing measurements in 1941 participants 23…”
Section: Methodsmentioning
confidence: 99%
“…13 Patients were asked to report the amount of time that they spent per week in the summer and winter on the following activities: walking, cycling, gardening, housekeeping, and sports. The mean number of hours spent at these activities per week in the summer and winter was calculated.…”
Section: Physical Activity Measuresmentioning
confidence: 99%
“…Eleven studies were conducted in a mixed-gender sample (20,25,26,30,32,33,43,44,(46)(47)(48), four among a male sample (34,36,40,41) and three studied females only (21,22,50). The average age of the study populations ranged from ~16-71 years, samples sizes varied from 19-2240.…”
Section: Construct Validitymentioning
confidence: 99%